The determinant factor of juvenile delinquency (path analysis model) - Tri Anjaswarni (Yinyang: Jurnal Studi Islam, Gender dan Anak)
There are many determinants of juvenile delinquency, one of them is technology. Technology is an integral part of modern society. However, misuse and uncontrolled use of technology may lead to negative impacts, one of which is juvenile delinquency. The objective of the study was to develop a determinant model of juvenile delinquency elicited from a path analysis. It was an observational study with a cross-sectional design. The sample size was 295 adolescents aged 12-19 years, consisting of adolescents at school and in the Juvenile Detention Centre (JDC). The data were taken a simple random sampling technique.. The analysis used Structural Equation Modelling. The determinants, which had a direct influence on juvenile delinquency were technology, peers, and lifestyle. Technology played a central role as the determinant that directly affected juvenile delinquency as many as 2.03 (203%). Digital technology may threaten adolescents as it can create and increase their delinquent behavior if its use is not controlled. The use of technology by adolescents needs to be supervised by parents and teachers together with nurses in community-based health practice.